Surviving High‐Temperature Calcination: ZrO2‐Induced Hematite Nanotubes for Photoelectrochemical Water Oxidation. (21st February 2017) - Li, Chengcheng; Li, Ang; Luo, Zhibin; Zhang, Jijie; Chang, Xiaoxia; Huang, Zhiqi; Wang, Tuo; Gong, Jinlong
Abstract: Nanotubular Fe2 O3 is a promising photoanode material, and producing morphologies that withstand high‐temperature calcination (HTC) is urgently needed to enhance the photoelectrochemical (PEC) performance. This work describes the design and fabrication of Fe2 O3 nanotube arrays that survive HTC for the first time. By introducing a ZrO2 shell on hydrothermal FeOOH nanorods by atomic layer deposition, subsequent high‐temperature solid‐state reaction converts FeOOH‐ZrO2 nanorods to ZrO2 ‐induced Fe2 O3 nanotubes (Zr‐Fe2 O3 NTs). The structural evolution of the hematite nanotubes is systematically explored. As a result of the nanostructuring and shortened charge collection distance, the nanotube photoanode shows a greatly improved PEC water oxidation activity, exhibiting a photocurrent density of 1.5 mA cm −2 at 1.23 V (vs. reversible hydrogen electrode, RHE), which is the highest among hematite nanotube photoanodes without co‐catalysts. Furthermore, a Co‐Pi decorated Zr‐Fe2 O3 NT photoanode reveals an enhanced onset potential of 0.65 V (vs. RHE) and a photocurrent of 1.87 mA cm −2 (at 1.23 V vs. RHE).